Medical data analysis based on Nao Robot: an automated approach towards robotic real-time interaction with human body - Sharif, Mhd Saeed; Alsibai, Mohammed Hayyan (IEEE, 2018)
There is a significant increase of strokes, heart diseases and premature death, people need more than ever to be aware of their vital signs such as blood pressure, heart beats, cholesterol level etc. Monitoring and analysing this medical data can help increase the awareness of the risk factor of heart disease. However, there is a huge pressure on medical staff and general practitioners (GPs), therefore this research proposes a medical data analysis based on Nao robots to meet these needs and it will serve as an automated approach towards a robotics real-time interaction with the human body. The proposed research offers a new way to allow users to understand the meaning of their vital signs using a human robot interaction. The developed system has been tested on publicly available data and simulated data. It can predict the future risk of heart disease based on some data attributes. Based on the risk prediction, it can feedback the result and the required lifestyle changes to avoid any related risk.